Sobre as Lipocalinas expressas em Rhodnius prolixus, um vetor da doença de Chagas - Daniela Viana dos Santos (2021)
The hematophagy process by arthropods has been one of the main targets of studies in the parasite-host interaction, and the kissing-bug Rhodnius prolixus, vector of the protozoan Trypanosoma cruzi, has been one of the main models for this research. Still in the 1980s, it was identified that, among the salivary proteins for disrupting vertebrate host homeostasis, lipocalins were among the most relevant proteins for this process. Since then, 38 lipocalins have been identified in the salivary glands of R. prolixus, including 19 nitrophorins (which act on vasodilation) and 19 lipocalins that act on different mechanisms to inhibit platelet aggregation. In 2014, an RNA sequencing of different tissues of R. prolixus was published, suggesting diversity and abundance of lipocalins. The present work aims to carry out a review of lipocalins from R. prolixus, combining transcriptome and genome data to annotate, structurally and evolutionarily, new lipocalins expressed in R. prolixus. For this, the lipocalins already known and the new transcripts, identified as lipocalins, were mapped to the genome using a BLAST tool. Identified new genes had their structure annotated with GeneWise. To infer an evolutionary orthological relationship between lipocalins, and to support the predicted functions for each lipocalin, all amino acid sequences (those existing in the literature and those recently identified) were used to construct phylogenetic trees. We identified a total of 29 new lipocalins, 5 of which were new vasodilators (all nitrophorins), 5 BAPs (which act to inhibit platelet aggregation and vasodilation), 11 inhibitors of platelet aggregation and 8 lipocalins belonging to a new family (apolyproteins) with function unknown. In addition, we observed that several of the lipocalins are also expressed in different R. prolxius tissues, including gut and reproductive organs. In addition to newly identified lipocalins and a mapping the new and old lipocalins in the genome of R. prolixus, our study also carried out a review on functional status and nomenclature of some of the already identified lipocalins. Our study reinforces that we are far from understanding the role of lipocalins in the physiology of R. prolixus, and that studies of this family are still of great relevance.